Analisis Pengendalian Kualitas Air Minum dalam Kemasan Menggunakan Metode FMEA dan Penerapan Kaizen (Study Kasus di PT.Lombok Pusaka Adam, Jelantik Lombok Tengah) - Lailatul Pahmi; Emmy Dyah Sulistiowati; Lisa Harsyiah (University of Mataram, 2022)
Clean water is one of the basic needs with unlimited use, even in the economic field. The opportunities provided can be utilized by companies that produce bottled drinking water. The existence of defective products is obtained in production so that the need for quality analysis of the product is still within the control limits on the P chart. This is done by knowing the highest value in the influential failure mode. So that suggestions for improvement with Kaizen can be given. Based on the control P chart obtained, all points of defective products in the production process are within control limits with a UCL limit of 0.00804 and an LCL limit of 0.00602. This indicates that the defective product is statistically controlled. The Failure Mode and Effect Analysis (FMEA) method assigns a priority value to each failure mode, and the value is the Risk Priority Number (RPN). The biggest RPN is that the cover does not stick to the surface of the cup, with an RPN value of 240. The proposed improvement using the Kaizen method is to increase inspections and routine repairs on the machine.